Frequency dependent fatigue behaviour of additively manufactured titanium lattices - Jones, AC; Jeffers, JRT; Oosterbeek, RN (Elsevier, 2023)
Additively manufactured (AM) porous titanium lattices, with their ability to match the mechanical properties of bone and avoid stress shielding, are a popular candidate material for orthopaedic implants. Such implants are now emerging as treatments for conditions like osteoarthritis and fixation of bone fractures. Fatigue tests are critical due to the cyclic loading environment and must be carried out at an accelerated loading rate to simulate many years of use. Tests are typically performed with servohydraulic instruments, which limits the cyclic compression to relatively low frequencies (15 Hz). Fatigue testing at a higher frequency would accelerate research, however, may introduce phenomena such as heat accumulation and strain rate effects. In this study the fatigue behaviour of a pure titanium stochastic lattice was determined at two test frequencies, 15 Hz and 110 Hz. Testing was conducted using an electromechanical dynamic system. The fatigue strengths at 106 cycles were 5.607 ± 0.106 MPa and 5.764 ± 0.214 MPa at 15 Hz and 110 Hz respectively. A hypothesis t-test at a 95% confidence level stated that there was significant evidence that the population means were not the same, demonstrating evidence of a difference in fatigue strength with testing frequency. However, we can conclude that the 2.8% increase in fatigue strength due to test frequency effects is inconsequential relative to the time saved (16 h per test) and typical batch-to-batch variability in fatigue strength of approximately 12%. The results of this study should help accelerate research into the fatigue properties of AM porous lattices.